Islamic Religious Learning in the Digital Age: An Interactive Method for Generation Z - Toni Ardi Rafsanjani; M. Abdurrozaq; Fauziah Inayati (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This research aims to explore and develop interactive and relevant Islamic religious learning methods for Generation Z in the digital era. Generation Z has unique characteristics, such as a high tendency towards technology, a practical and visual learning style, and the need to get information instantly. Given these needs, conventional learning approaches are considered less effective in attracting their interest in exploring Islam. This study uses a qualitative research method with data collection techniques through in-depth interviews, observations, and literature studies related to digital learning methods and religious teaching. Participants in this study include students, Islamic teachers, and experts in the field of digital education. The results of the study show that technology-based interactive methods, such as learning apps, educational short videos, interactive quizzes, and discussions on social media platforms, can increase the interest and engagement of Generation Z in learning Islam. The use of digital media not only makes the learning process more interesting but also helps students understand religious concepts in a more applicable and relevant way to daily life. In addition, the application of gamification, augmented reality (AR), and virtual reality (VR) in Islamic religious learning shows great potential to enhance immersive and contextual learning experiences. The implications of this study are the need for the integration of digital technology in the Islamic religious learning curriculum, as well as training for educators so that they can use interactive methods effectively. The novelty of this study lies in a holistic approach that combines digital interactive methods with religious learning, which has not been widely applied in the context of Islamic education. This research is expected to be a reference for educators and curriculum developers in creating Islamic religious learning strategies that are more adaptive, interactive, and able to answer the unique needs and characteristics of Generation Z.